Global Market and Trade - Miciuła, Ireneusz (Business, Management and Economics, 2023)
Global Market and Trade provides knowledge, recommendations, and practical solutions to new challenges within the contemporary processes of globalization and international trade. It examines the issues of contemporary foundations of the global market and trade based on the development of information technology and new geopolitical and religious conditions. Chapters address such topics as ITC technology and the rules of financial flows, the cultural and religious conditions of world markets and trade, the impact of development inequality on policy in emerging economies, and much more.